THE INFLUENCE OF PROACTIVE PERSONALITY ON PERCEIVED CAREER SUCCESS: INTERNAL AND EXTERNAL NETWORKING BEHAVIOR AS MEDIATING VARIABLES - Tanzila, Lita Rizky; Sudjadi, Achmad; Purnomo, Ratno (Performance, 2016)
The aims of this research were to investigate the influence of proactive personality on perceived career success, proactive personality on internal as well as external networking behavior, the influence of internal as well as external networking behavior on perceived career success, and to investigate the role mediating of internal as well as external networking behavior on relationship between proactive personality and perceived career success. This research was conducted at PD BPR BKK Purbalingga. Target population of this research was all employees in centre office and branch office which comprise of 129 people. This research used survey method with simple random sampling as sampling technique. Based on the calculation with Slovin formula, the sample size was 98 respondents. Furthermore, the technique of data analysis applied in this study was multiple regressions. Based on the result of data analysis, it could be concluded that proactive personality had positive and significant influence to perceived career success. Proactive personality has positive and significant influence to internal as well as external networking behavior. Internal and external networking behavior had positive and significant influence to perceived career success. Furthermore, internal as well as external networking behavior partially mediated between the relationship of proactive personality and perceived career success.